Analysis of Infertility Factors Caused by Gynecological Chronic Pelvic Inflammation Disease Based on Multivariate Regression Analysis of Logistic. (16th June 2022) - Liu, Linmei; Yang, Gang; Ren, Jigang; Zhang, Limei; Wu, Ting; Zheng, Qiao
Abstract : In order to solve the complex and recurrent problem of chronic pelvic inflammation disease (CPID) in the process of the clinical treatment, a method of understanding the influencing factors of CPID by investigating the actual situation of clinical cases and using logistics regression analysis was proposed in this study. A total of 204 outpatients were selected from a certain hospital. The ratio of the cases in the experimental group to those in the control group stands at 1 : 1. The results were obtained as follows. According to the data of CPID patients collected in the paper, the majority of patients had a high school education background or below technical secondary school education background, accounting for 66.7%. And the majority of patients were manual workers, accounting for 69.1%. All the exp (B ) values of the frequency of sex life per month ≥ 9 times, frequent sex life during menstruation, IUD contraception, no contraception, abortion ≥ 3 times, vaginal irrigation per week ≥ 1 time, and intrauterine surgery ≥ 3 times were more than 1. These seven factors were the risk factors for chronic pelvic inflammation. Oral contraceptives were a weak protective factor of chronic pelvic inflammation. These factors including early drug withdrawal (53.1%), without understanding the condition of the disease (35.7%), no time to review the disease (24.5%), and irregular medication (21.4%) accounted for a large proportion. They were associated with the recurrence of CPID. This method is aimed at providing some foundations for establishing effective prevention and control measures for chronic pelvic inflammation and providing a recognized clinical diagnosis and efficacy evaluation criteria for the treatment of chronic pelvic inflammation.